Two years of optical and NIR observations of the superluminous supernova UID 30901 discovered by the UltraVISTA SN survey. Issue 2 (20th April 2022) - Hueichapan, E D; Contreras, C; Cartier, R; Lira, P; Sanchez-Saez, P; Milvang-Jensen, B; Fynbo, J P U; Anderson, J P; Hamuy, M
ABSTRACT: We present deep optical and near-infrared photometry of UID 30901, a superluminous supernova (SLSN) discovered during the UltraVISTA survey. The observations were obtained with VIRCAM ( YJHKs ) mounted on the VISTA telescope, DECam ( griz ) on the Blanco telescope, and SUBARU Hyper Suprime-Cam (HSC; grizy ). These multiband observations comprise +700 d making UID 30901 one of the best photometrically followed SLSNe to date. The host galaxy of UID 30901 is detected in a deep HST F814W image with an AB magnitude of 27.3 ± 0.2. While no spectra exist for the SN or its host galaxy, we perform our analysis assuming z = 0.37, based on the photometric redshift of a possible host galaxy found at a projected distance of 7 kpc. Fitting a blackbody to the observations, the radius, temperature, and bolometric light curve are computed. We find a maximum bolometric luminosity of 5.4 ± 0.34 × 10 43 erg s −1 . A flattening in the light curve beyond 600 d is observed and several possible causes are discussed. We find the observations to clearly favour an SLSN type I, and plausible power sources such as the radioactive decay of 56 Ni and the spin-down of a magnetar are compared to the data. We find that the magnetar model yields a good fit to the observations with the following parameters: a magnetic field B = 1.4 ± 0.3 × 10 14 G, spin period of P = 6.0 ± 0.1 ms, and ejecta mass $M_{ ej} = 11.9^{+4.8}_{-6.4} \, M_{\odot }$ .